Creation of a culture that generates aggregate value in coffee activity (2019)
The article tries to establish the relationship between the historical and culturalprocess that allowed the development of the coffee economy and marketingmethods focused on the raw materials market, without generating addedvalue. The processes of industrialization and technification of coffee and itsexpressions in the so-called special coffee, pose great challenges and a culturaltransformation in the forms of marketing and especially in production systems.The quality requirements affect all the activity and social environment of thecoffee production unit